2011
DOI: 10.1007/s00424-011-0924-7
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine residue 911 in C-terminal tail of human BKCaα channel subunit is crucial for its activation by carbon monoxide

Abstract: The large conductance, voltage- and calcium-activated potassium channel, BK(Ca), is a known target for the gasotransmitter, carbon monoxide (CO). Activation of BK(Ca) by CO modulates cellular excitability and contributes to the physiology of a diverse array of processes, including vascular tone and oxygen-sensing. Currently, there is no consensus regarding the molecular mechanisms underpinning reception of CO by the BK(Ca). Here, employing voltage-clamped, inside-out patches from HEK293 cells expressing single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 31 publications
0
43
1
Order By: Relevance
“…However, how heme binds and whether CO stimulates K ϩ efflux in a heme-dependent or heme-independent manner has still to be established. A cytochrome c-type CXXCH motif is present rather than the typical HRM (45)(46)(47)(48). Further studies are also required to establish the physiological relevance of the apparent heme-mediated inhibition of the arginine transferase activity of R-transferase and of putative heme binding to stanniocalcin glycoprotein hormones (52)(53)(54).…”
Section: Non-nr Heme Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, how heme binds and whether CO stimulates K ϩ efflux in a heme-dependent or heme-independent manner has still to be established. A cytochrome c-type CXXCH motif is present rather than the typical HRM (45)(46)(47)(48). Further studies are also required to establish the physiological relevance of the apparent heme-mediated inhibition of the arginine transferase activity of R-transferase and of putative heme binding to stanniocalcin glycoprotein hormones (52)(53)(54).…”
Section: Non-nr Heme Sensorsmentioning
confidence: 99%
“…Studies on a peptide containing the CXXCH motif (which binds heme by His coordination) led to a conclusion that heme is the CO-binding site (45). However, mutating the CXXCH motif His did not diminish the effect of CO on channel permeability (despite heme loss), possibly because CO might also interact with an unidentified metal cluster (46,47). It was also proposed that BK channels do not bind heme but that CXXCH motif cysteines form a thiol/disulfide redox switch, similar to that proposed for Rev-erb␤ (48).…”
Section: Cellular Homeostasismentioning
confidence: 99%
“…Moreover, a recent report suggests the involvement of ATP-dependent (K ATP ) potassium channels as part of the dilatatory mechanisms exerted by CORM-3 [13]. However, other authors report the central role of the KCa,α in CO effect [25,28,29].…”
Section: Discussionmentioning
confidence: 89%
“…A number of research groups, including our own, have demonstrated that specific ion channels are targets of regulation by CO, and that via ion channel modulation CO exerts many of its important physiological and pathological actions (Williams et al 2004;Jaggar et al 2005;Telezhkin et al 2011;Scragg et al 2008;Dallas et al 2012;Peers et al 2014). In the present study, we have examined whether T-type Ca 2+ channels represent another target for modulation by CO and, if so, how this might impact on VSMC proliferation.…”
Section: Xx2 Introductionmentioning
confidence: 81%